The Bourne Imperative - Lustbader, Eric Van (Orion Books Ltd, 2012)
Jason Bourne pulls a drowning man from a lake - a man not only freezing, but bleeding profusely from a gun-shot wound. He wakes as an amnesiac, with no memory of who he is or why he was shot$1! = (BAnd Bourne is eerily reminderd of his own past. Meanwhile, Mossad agent Rebekah is so determined to find this man that she's gone off the grid, cut her ties to her agency, and risks a summary execution if caught by her former colleagues. And back in the U.S., a new agent has been recruited - but does he have a secret mission of his own?...s
Keywords: Fiction